Cost-effectiveness of tolvaptan for the treatment of hyponatraemia secondary to syndrome of inappropriate antidiuretic hormone secretion in Sweden. Issue 1 (December 2016) - Jamookeeah, Clare; Robinson, Paul; O'Reilly, Karl; Lundberg, Johan; Gisby, Martin; Ländin, Michael; Skov, Jakob; Trueman, David
Abstract Background Tolvaptan is the only vasopressin V2 receptor antagonist licensed by the European Medicines Agency for the treatment of hyponatraemia (HN) secondary to the syndrome of inappropriate antidiuretic hormone secretion (SIADH). We have investigated the cost-effectiveness of tolvaptan versus no active treatment (NAT) in adult patients within the licensed indication who have either failed to respond to fluid restriction or for whom the use of fluid restriction is not suitable, from the societal perspective in Sweden. Methods A cost-utility analysis, considering a 'general SIADH' population and two subpopulations of patients (small-cell lung cancer [SCLC] and pneumonia) to broadly represent the complex clinical pathway of SIADH, was performed. A discrete event simulation was developed to model the progression of individuals through inpatient admissions over a 30-day time horizon (180 days for the SCLC cohort). Clinical data were derived from tolvaptan trials and observational data sources. All costs are given in Swedish kronor (SEK). Results In the 'general SIADH' population, tolvaptan was associated with reduced costs (SEK 5, 779 per patient [€624]) and increased quality-adjusted life-years (QALYs) (0.0019) compared with NAT and was therefore the dominant treatment strategy. Tolvaptan was also associated with reduced costs and increased QALYs in the SCLC and pneumonia subpopulations. The most influential variables in our analysis were reduction in hospital length of stay, duration of treatment and long term treatment with tolvaptan in SCLC patients. Conclusions Tolvaptan represents a cost-effective treatment option in Sweden for hospitalised patients with HN secondary to SIADH who have either failed to respond to or are unsuitable for fluid restriction.